MODEL MATEMATIKA SS_M IR PADA PENYEBARAN COVID-19 DENGAN PENERAPAN PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) DI JAWA TENGAH - Feriastuti, Erina Tri; Adi, Yudi Ari (Unnes Journal of Mathematics, 2021)
Coronavirus or COVID-19 which was first discovered in China in Desember, 2019. COVID-19 is an infectious disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-Cov-2). WHO declared COVID-19 a pandemic on March 11, 2020. This virus spreads rapidly because the transmission is directly from human to other human. An understanding of the spread of COVID-19 important to determine policies in control of the spread of COVID-19. In this research, a simple mathematical model of the spread of COVID-19 in era PPKM and the model is validated against data from Jawa Tengah, Indonesia from August 1, 2021, to August 31, 2021. In this simulation has been a sensitivity analysis of model to determine the influential parameters on the basic reproduction number (R0) . Based on the numerical solution sensitivity analysis the results show that interaction rate are the most influential parameters on R0. From the result research it can be concluded that implementation of PPKM in Central Java Province was successful because it can reduce the number of population infected with COVID-19 in Central Java, which is needs to reduce community activities or mobality and control the implementation of PPKM so that there is no spike in cases infected of COVID-19 in Central Java.